Estudio avifaunístico del barrio Arrayampata parroquia Angamarca cantón Pujilí provincia de Cotopaxi - Mejía Riera, José Luis (2016)
The present research analysed birds abundance and diversity at Arrayampata neighbourhood, Pujilí canton, Cotopaxi Province from May to August 2016. It was done by the establishment of transects and temporary observatories. As a result a total of 22 species were registered, which represents 9 orders and 16 families. The study area was subdivided in three zones according to the altitudinal gradient. The abundance of species represented 16, 48,38 to 35, 48 % in each lower, central and high zone, respectively being the predominating order the Passeriformes one. As a result of the research a field guide of bids was made in order to provide specific information of the registered species according to the areas where those were found. Information like order, family and names (scientific, common, spanish and english) are detailed in the guide as well as a brief description of each specie.